Developmental stage-specific regulation of the circadian clock by temperature in Zebrafish - Lahiri, Kajori; Fröhlich, Nadine; Foulkes, Nicholas S. (BioMed research international, 2014)
The circadian clock enables animals to adapt their physiology and behaviour in anticipation of the day-night cycle. Light and temperature represent two key environmental timing cues (zeitgebers) able to reset this mechanism and so maintain its synchronization with the environmental cycle. One key challenge is to unravel how the regulation of the clock by zeitgebers matures during early development. The zebrafish is an ideal model for studying circadian clock ontogeny since the process of development occurs ex utero in an optically transparent chorion and many tools are available for genetic analysis. However, the role played by temperature in regulating the clock during zebrafish development is poorly understood. Here, we have established a clock-regulated luciferase reporter transgenic zebrafish line (Tg (−3.1) per1b::luc) to study the effects of temperature on clock entrainment. We reveal that under complete darkness, from an early developmental stage onwards (48 to 72 hpf), exposure to temperature cycles is a prerequisite for the establishment of self-sustaining rhythms of zfper1b, zfaanat2, and zfirbp expression and also for circadian cell cycle rhythms. Furthermore, we show that following the 5-9 somite stage, the expression of zfper1b is regulated by acute temperature shifts.
Gesehen am 09.08.2017